KEPUTUSAN INDIVIDU USIA KERJA UNTUK BERMIGRASI: BUKTI DARI DATA LONGITUDINAL DI JAWA TIMUR - Arbain Agus Wijaya; Munawar Ismail; Arif Hoetoro (Research Centre for Population, Indonesian Institute of Sciences, 2019)
Migration is not only limited because of the driving and pulling factors from the area of origin and destination. Individual socio-economic factors are important factors that determine the decision to migrate. This study aims to analyze the influence of individual socio-economic factors on migration in East Java Province. The panel data used are longitudinal data from the Indonesian Family Life Survey (IFLS)-4 and the IFLS-5. In this study, the individual social factors consisted of age, sex, education, marital status, family size, and residence characteristics. Moreover, the individual economic factors comprise land ownership for agriculture, ownership of health insurance, loan ownership, and poverty status. By employing the binary logistic regression analysis, we found that migration in the population of East Java Province was influenced by age, marital status, education, and characteristics of residence as social factors as well as agricultural land ownership and health insurance ownership as economic factors.